The moderating effects of organizational support on the relationship between job stress and nurses’ performance in public sector hospitals in Saudi Arabia - Al-Homayan, Abdullah Mohammad; Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan; Islam, Rabiul (AENSI Publisher, 2013)
Organizational support is based on the observation that when the leadership and management of an organization show concern about the commitment of the employees towards the organization. With organizational support, nurses are able to succeed in continuing their professional development. The aim of the study is to evaluate the moderating effect of organizational support on the relationship between job stress and nurses’ performance.In order to achieve the study objective, a survey conducted.Questionnaires distributed to the public sector hospital’s manager in Saudi Arabia.The findings of the study turn out to be true; the study will contribute to both theory and practice.Through the present study, the researcher expects the findings to shed light on the research conducted regression to analysis using organizational support as a moderator in a relationship between job stress and nurses’ job performance.